(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article analyzes the socio-philosophical ideas of the enlightener Abdurauf Fitrat, one of the representatives of Jadidism, in his treatise "Oriental Politics", including the issues of moral decline and social responsibility.